Biology of aging - McDonald, Roger B.
Biology of Aging presents the biological principles that have led to a new understanding of the causes of aging and describes how these basic principles help one to understand the human experience of biological aging, longevity, and age-related disease. Intended for undergraduate biology students, it describes how the rate of biological aging is measured; explores the mechanisms underlying cellular aging; discusses the genetic pathways that affect longevity in various organisms; outlines the normal age-related changes and the functional decline that occurs in physiological systems over the lifespan; and considers the implications of modulating the rate of aging and longevity. The book also includes end-of-chapter discussion questions to help students assess their knowledge of the material